Complications of Limbal Stay Sutures in Strabismus Surgery. (3rd July 2021) - Kuruvilla, Shilpa Elizabeth; Pater, John; Taranath, Deepa
ABSTRACT: Introduction : The use of limbal stay sutures is a well-established and frequently used technique to assist in intraoperative globe manipulation. As they are removed at the termination of the surgical procedure, they are presumed to be innocuous and not associated with significant postoperative complications. Methods : We describe two cases presenting to the same tertiary care center for the management of their complications post strabismus surgery, the causative factor in both cases being the stay sutures used during the surgical procedure. The clinical details of each case are discussed, followed by a literature review. Cases : Case 1 showed evidence of epithelial ingrowth into the cornea from the stay suture site. This case, previously reported by the senior author, is now described over an eight-year period, along with clinical photographs. Case 2 developed microbial keratitis and postoperative endophthalmitis with the locus at the stay suture site. Discussion : Complications of stay suture are rare but can occur, with potentially blinding sequelae. It is important to be aware of these risks and consider alternate methods of globe traction during strabismus surgery.